Las actividades rítmicas con música mediante el juego para desarrollar la expresión corporal en niños de 4 - 5 años de la escuela de educación básica Prof. Julio Servio Ordóñez Espinosa” de la ciudad de Loja, período 2014 -2015. - Flores Jiron, Lucia Bernarda (2016)
This research titled: Rhythmic ACTIVITIES WITH MUSIC THROUGH THE GAME TO DEVELOP THE CORPORAL EXPRESSION IN CHILDREN AGED 4-5 YEARS BASIC EDUCATION SCHOOL "PROF. SERBIAN ORDÓÑEZ ESPINOSA JULIO "LOJA CITY, PERIOD 2014 -2015. It focuses on the problems detected by the influence of rhythmic music activities through play to develop body expression through its objectives under develop, implement and evaluate a set of games with music to develop body expression. It is characterized by the following methods: Scientific, inductive-deductive and statistical. Survey techniques and observation sheets diagnosis and testing applied by the scientific process, teachers and children are the axis that determine the initial results of the problem therefore consists of a set of games with music to develop body expression as an alternative solution, valued the program as effective on the basis of the evaluation results of the survey and final observation sheets. With all the arsenal of information of the results we reach the following conclusions. As needs a correct planning so that children can recognize body parts, should also be acquisition and adaptation of time by musical rhythms. Recommendations: Determine the need to establish an appropriate methodological strategy, which allows the child to recognize each of the parts of your body, motivating children and build teaching and learning processes in order to develop body expression.